SELF-REALIZATION IN ENTREPRENEURSHIP OF FUTURE ENGINEERING SPECIALISTS - Bazyl, Liudmyla; Ostenda, Aleksander; Peliova, Jana; Orlov, Valerii; Nestorenko, Tetyana (Profesìjna pedagogìka, 2023)
Relevance: professional preparation of future specialists of engineering specialities takes place in technical establishments of higher education of Europe, mostly, after one of two strategies (specialized activity or administration) and directly does not envisage preparation of bread-winners of higher engineering education to self-realization in an enterprise; however under modern circumstances of civilization advancement a self enterprise can be the most effective and effective method of self-realization of specialists of engineering profession. The purpose of the article was to characterize the features of stimulating the training of engineering graduates for self-realization and starting their own business based on the analysis of the entrepreneurial experience of engineers and educational programs for the professional training of future specialists in engineering specialties. Methods:  the research methodology is represented by the integrity of person-oriented, subject-activity, competence, synergistic, existential-phenomenological, environmental, and integrative approaches, which made it possible to maximally take into account the sectoral specificity of engineering, the peculiarities of the process of obtaining an engineering education, the complexity of integrating the professional and entrepreneurial activities of an engineer. Results: the ideas regarding the training of future specialists in engineering specialties to open and successfully implement a business are substantiated. Conclusions. A conclusion was made about the need to implement an entrepreneurial component in the professional training of future specialists in engineering specialties, which will contribute to the actualization and development of their individual and personal qualities for starting their own business and successfully promoting their own business. The obtained results can become the basis for further scientific substantiation of the content and innovative technologies of training students of engineering education for self-realization in innovative entrepreneurship, as well as the introduction of game methods, business accelerators, simulators, and simulators. Актуальність: професійна підготовка майбутніх фахівців інженерних спеціальностей у технічних закладах вищої освіти Європи відбувається, здебільшого, за однією з двох стратегій (спеціалізована діяльність чи адміністрування) й безпосередньо не передбачає підготовку здобувачів вищої інженерної освіти до самореалізації в підприємництві; однак за сучасних обставин цивілізаційного поступу саме підприємництво може бути найбільш дієвим і ефективним способом самореалізації спеціалістів інженерного фаху. Мета: охарактеризувати особливості стимулювання підготовки майбутніх фахівців інженерних спеціальностей до самореалізації, у т.ч. започаткування власного бізнесу, на основі аналізу кращих практик підприємництва в сфері інженерії й розгляду освітньо-професійних програм підготовки молодших спеціалістів інженерного фаху. Методи: методологія дослідження представлена концептуальними положеннями особистісно-орієнтованого, екзистенційно-феноменологічного, компетентнісного, середовищного й інтегративного підходів, що дало змогу врахувати галузеві особливості інженерії, зокрема машинобудування, цільові, змістові й організаційні особливості освітнього процесу у закладах вищої інженерної освіти. Результати: обґрунтовано теоретичні ідеї щодо забезпечення якості підготовки майбутніх фахівців інженерних спеціальностей до самореалізації, зокрема на основі самозайнятості й успішної реалізації бізнесу. Висновки. Підприємницька складова є необхідною компонентою професійної підготовки молодших спеціалістів інженерного фаху, що сприятиме актуалізації та розвитку їхніх особистісно-підприємницьких якостей щодо відкриття й успішного просування власної справи. Отримані результати можуть стати основою для подальшого наукового обґрунтування змісту та інноваційних технологій підготовки здобувачів інженерної освіти до самореалізації в інноваційному підприємництві, а також запровадження ігрових методів, бізнес-акселераторів, тренажерів та симуляторів.